Pemerolehan Bahasa Anak Usia 4–5 Tahun dalam Menceritakan Gambar Berseri: Kajian Psikolinguistik - Farikul Hasan; Listiyani Listiyani; Nailatus Sa adah; Hodairiyah Hodairiyah (JURNAL ILMIAH PENELITIAN MAHASISWA, 2026)
Language acquisition is a natural process experienced by children from birth through interaction with their surrounding environment. Between the ages of 4 and 5, children's language abilities develop rapidly, characterized by an increasing capacity to construct simple sentences, comprehend the meaning of utterances, and recount events in a coherent sequence. This study aims to describe the language acquisition of 4- to 5-year-old children as they narrate stories based on a series of pictures, utilizing a psycholinguistic perspective. A qualitative descriptive method was employed, incorporating observation, listening, recording, and note-taking techniques. The data consisted of the children's spoken narratives regarding the picture series. The results indicate that children in this age group are capable of accurately using nouns, verbs, and adjectives; constructing simple sentence patterns; and linking events coherently. From a psycholinguistic perspective, these abilities reflect development in cognitive, syntactic, and semantic aspects, all of which are influenced by the children's linguistic environment and communication experiences